Implicit and implicit-explicit Lagrange-projection finite volume schemes exactly well-balanced for 1D shallow water system - Caballero-Cárdenas, C; Castro-Díaz, Manuel Jesús; Morales-de-Luna, Tomás (Elsevier, 2022)
In this paper we consider the Lagrange-Projection technique in the framework of finite volume schemes applied to the shallow water system. We shall consider two versions of the scheme for the Lagrangian step: one fully implicit and one implicit-explicit, based on how the geometric source term is treated. First and second order well-balanced versions of the schemes are presented, in which the water at rest solutions are preserved. This allows to obtain efficient numerical schemes in low Froude number regimes, as the usual CFL restriction driven by the acoustic waves is avoided.
Keywords: Método de los volúmenes finitos; Lagrange, Ecuaciones de; Lagrangian-projection technique; IMEX schemes; Well-balanced; Shallow-water